Dual isolation of primary neurons and oligodendrocytes from guinea pig frontal cortex - Moloney, Roisin A.; Pavy, Carlton L.; Kahl, Richard G. S.; Palliser, Hannah K.; Hirst, Jon J.; Shaw, Julia C. (Frontiers in Cellular Neuroscience, 2024)
Primary cell culture is a technique widely used in neuroscience research to investigate mechanisms that underlie pathologies at a cellular level. Typically, mouse or rat tissue is used for this process, however altricial rodent species have markedly different neurodevelopmental trajectories comparatively to humans. The use of guinea pig brain tissue presents a novel aspect to this routinely used cell culture method, whilst also allowing for dual isolation of two major cell types from a physiologically relevant animal model for studying perinatal neurodevelopment.Primary neuronal and oligodendrocyte cell cultures were derived from fetal guinea pig frontal cortex brain tissue at gestational age 62 (GA62); which is a key time in neuronal and oligodendrocyte development. The major advantage of this protocol is the ability to acquire both neuronal and oligodendrocyte cellular cultures from the frontal cortex of one fetal brain. Briefly, neuronal cells were grown in 12 well plates initially in a 24-hour serum rich media to enhance neuronal survival, before switching to a serum-free media formulation. Oligodendrocytes were first grown in cell culture flasks, using a serum rich media which enabled growth of oligodendrocyte progenitor cells (OPC's) on an astrocyte bed. Following confluency, the shake method of differential adhesion and separation was utilized via horizontal shaking of the OPC's off the astrocyte bed overnight. From there, OPC's were plated in 12 well plates and were initially expanded in a media supplemented with growth hormones, before switching to maturation media to progress the lineage to a mature phenotype. RT-PCR of key population markers were performed on both cell culture types, with immunocytochemistry further validating these populations.2 This is a provisional file, not the final typeset article experiments to occur and may be useful particularly in studying neurodevelopmental conditions with perinatal origins.